1996
DOI: 10.1006/lmot.1996.0025
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Discrete Signal on Context Conditioning: Assessment by Preference and Freezing Tests

Abstract: Four experiments with rats assessed conditioning to contextual cues after the delivery of footshocks that were either signaled by a discrete stimulus or unsignaled. Two different tests were used. The first was a context preference test in which subjects were allowed to move freely in a brightly lit, unconditionally aversive context and the former shock context. The second test consisted of scoring freezing behavior while the animals were confined to the former conditioning context. During context preference te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
1
1
Order By: Relevance
“…Some of our own indirect evidence suggests that these C57/bl6 mice extinguish context fear faster than cue fear (Cain et al 2002). However, other investigators have also failed to find increases in context freezing with more CS-alone presentations in experiments designed to reveal them (Maes and LoLordo 1996), and we have been unable to find any observations of this expected reciprocal increase in context conditioning with degraded CS contingency. Thus, while the orderly pattern of decreasing response to the cue with reduced contingency in our experiments suggests that cue competition should have taken place, it was not expressed as context freezing.…”
Section: Discussioncontrasting
confidence: 60%
“…Some of our own indirect evidence suggests that these C57/bl6 mice extinguish context fear faster than cue fear (Cain et al 2002). However, other investigators have also failed to find increases in context freezing with more CS-alone presentations in experiments designed to reveal them (Maes and LoLordo 1996), and we have been unable to find any observations of this expected reciprocal increase in context conditioning with degraded CS contingency. Thus, while the orderly pattern of decreasing response to the cue with reduced contingency in our experiments suggests that cue competition should have taken place, it was not expressed as context freezing.…”
Section: Discussioncontrasting
confidence: 60%
“…However, he observed substantial though incomplete overshadowing after 12 sessions. Moreover, in an experiment otherwise like Experiment 2, but with a single conditioning session, there was no overshadowing of situational cues by the discrete CS even with variable intervals between trials (see also Maes & LoLordo, 1996). Whether more conditioning trials in the one trial per session procedure of Experiment 1 would have revealed overshadowing in the variable time groups remains to be seen.…”
Section: Discussionmentioning
confidence: 84%